فاعلية برنامج قائم على السيكودراما لخفض السلوك العدواني لدى الأطفال ضعاف السمع - السيد، سعد فايز سعد; حنور، قطب عبده خليل; العطار، محمود مغازي (جامعة كفر الشيخ - كلية التربية, 2018)
تهدف هذه الدراسة إلى: التحقق من فاعلية برنامج قائم على السيكودراما لخفض السلوك العدواني لدى الأطفال ضعاف السمع، ومعرفة استمرارية تأثير البرنامج السيكو درامي لخفض السلوك العدواني لدى أطفال المجموعة التجريبية. وتكونت عينة الدراسة من: (٢٠) طفلا ممن لديهم ضعف في السمع وتتراوح أعمارهم الزمنية (9-١٢) سنوات. وتمثلت أدوات الدراسة في: مقياس السلوك العدواني، ومقياس المهارات الاجتماعية للأطفال، البرنامج السيكو درامي. وأسفرت النتائج الدراسة عن: وجود فروق ذات دلالة إحصائية بين متوسط رتب درجات أفراد المجموعة الضابطة والتجريبية على مقياس السلوك العدواني بعد تطبيق البرنامج في اتجاه المجموعة الضابطة، وجود فروق ذات دلالة إحصائية بين متوسط رتب درجات أفراد المجموعة التجريبية على مقياس السلوك العدواني في القياسيين (القبلي والبعدي) في اتجاه القياس القبلي، وجود فروق ذات دلالة إحصائية بين متوسط رتب درجات أفراد المجموعة الضابطة والتجريبية على مقياس المهارات الاجتماعية بعد تطبيق البرنامج لصالح المجموعة التجريبية، وجود فروق ذات دلالة إحصائية بين متوسط رتب درجات أفراد المجموعة التجريبية على مقياس المهارات الاجتماعية في القياسيين (القبلي والبعدي) لصالح القياس البعدي، عدم وجود فروق ذات دلالة إحصائية بين متوسط رتب درجات أفراد المجموعة التجريبية على مقياس السلوك العدواني بين القياسيين (البعدي والتتبعي)، عدم وجود فروق ذات دلالة إحصائية بين متوسط رتب درجات أفراد المجموعة التجريبية على مقياس المهارات الاجتماعية بين القياسيين (البعدي والتتبعي).
The aim of this study is to: investigate the effectiveness of a program based on Psychodrama to develop social skills and reduce the aggressive behavior of children with hearing loss, and to know the continuity of the impact of the program to develop social skills and reduce aggressive behavior in children of the experimental group. The sample of the study consisted of: (20) children and children with hearing impairment and age range (9 - 12) years. The tools of the study were: The measure of aggressive behavior, and the measure of the social skills of children, the psychodrama program. The results of the study revealed: There were statistically significant differences between the average grade of the control group and the experimental group on the measure of aggressive behavior after the application of the program in the direction of the control group. There were statistically significant differences between the average grade of the experimental group on the aggressive behavior scale in the tribal In the direction of tribal measurement, there were statistically significant differences between the average grade of the control group and the experimental group on the social skills scale after applying the program for the experimental group. There were statistically significant differences between the average grades The absence of statistically significant differences between the average grade of the experimental group on the measure of aggressive behavior between the two dimensions (post and sequential), the absence of statistically significant differences between the average grade The scores of the members of the experimental group on the scale of social skills between the criteria (dimension and follow-up ).
Keywords: الصحة النفسية -- الرعاية الإجتماعية -- علم النفس السلوكي -- السلوك العدواني -- الأطفال ضعاف السمع -- مستخلصات الأبحاث